Assessment of Suitability of Plant Communities of Pole and Tree Standa at Several Main Roads in Sumber Village, Indonesia - Utomo, Alifia Namira; Naluri Allobua, Brighia Sastrani; Paramita, Feninta Setyaning; Sari, Indah Puspita (Innovative: Journal Of Social Science Research, 2024)
Vegetation along the main urban roads plays an important role in improving sustainable environments. The study aims to evaluate the suitability of plant communities along the main roads of Sumber Village, Surakarta to support green infrastructure. The study was conducted by collecting primary data through field surveys, as well as through literature studies. The analysis used scores based on silviculture, management, and aesthetic aspects. The results showed that there were 21 species from 13 families, with a dominance of tree-habitus species compared to poles. Species such as Mangifera indica and Handroanthus chrysotrichus scored high due to their tolerance to urban conditions and easy maintenance. In contrast, species such as Artocarpus altilis and Cyrtostachys renda scored lower. Most species have a conservation status of Least Concern, although Pterocarpus indicus is listed as Endangered. Vegetation in Sumber Village overall supports ecological sustainability, but species with threatened conservation status require special attention. The selection of plants that are suitable for urban conditions is very important to create a healthy and aesthetic environment.